Validity-Reliability Test of Indonesian-translated MBD-MBS questionnaire as screening method for mouth breathers - Winastuti, Retno Arun; Ratunanda, Sinta Sari; Wijana, Wijana (Oto Rhino Laryngologica Indonesiana, 2023)
Introduction Mouth breathing, the process of air entry from the mouth to the lungs without passing through the nose, is an abnormal behaviour that may imply the presence of a comorbidity. Mouth breathing in children, teenagers, and adults leads to numerous pathological consequences, especially in children. There are several methods available to diagnose mouth breathing, one of them being the provision of questionnaires, however, there is yet any mouth breathing questionnaire that has been translated into Indonesian. Therefore, this research aims to translate the MBD-MBS questionnaire in Indonesian, and conduct a validity and reliability test for the translated questionnaire. Hence, this translated questionnaire may be used as a tool to diagnose the presence of mouth breathing. Methods This cross-sectional study was conducted to 33 parents of children in day-cares or preschools in Bandung city that fulfilled the inclusion and exclusion criteria. Translation of the questionnaire was conducted by a sworn translator after permission was granted by the original author through email. The questionnaire was then distributed to the subjects after being given consent. Afterwards, the validity and reliability test were then conducted using Spearman and Cronbach-α formulas respectively.   Results All six questions in the Indonesian translated MBD-MBS questionnaire is validated (rcount > rtable, which is 0.355) and reliable (Cronbach’s Alpha 0.643 > 0.6). Conclusion Based on both validity and reliability tests, all questions in the Indonesian-translated MBD-MBS questionnaire are considered valid and reliable. Hence, this questionnaire is suitable to be utilized for further studies about mouth breathing.